2009
DOI: 10.1523/jneurosci.5834-08.2009
|View full text |Cite
|
Sign up to set email alerts
|

Lateral Gain Control in the Outer Retina Leads to Potentiation of Center Responses of Retinal Neurons

Abstract: The retina can function under a variety of adaptation conditions and stimulus paradigms. To adapt to these various conditions, modifications in the phototransduction cascade and at the synaptic and network levels occur. In this paper, we focus on the properties and function of a gain control mechanism in the cone synapse. We show that horizontal cells, in addition to inhibiting cones via a "lateral inhibitory pathway," also modulate the synaptic gain of the photoreceptor via a "lateral gain control mechanism."… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 41 publications
2
28
0
Order By: Relevance
“…We have stimulated the retina with a similar stimulus and studied the responses of cones and ganglion cells (GCs). We found that the response of GCs and the output of cones to a flickering spot became larger with steady surround illumination [63]. This suggests that the psychophysical phenomenon described by Kelly could have an outer retinal origin and that it is a fundamental feature of the vertebrate visual system.…”
Section: General Neuronal Processing In the Outer Plexiform Layermentioning
confidence: 50%
See 1 more Smart Citation
“…We have stimulated the retina with a similar stimulus and studied the responses of cones and ganglion cells (GCs). We found that the response of GCs and the output of cones to a flickering spot became larger with steady surround illumination [63]. This suggests that the psychophysical phenomenon described by Kelly could have an outer retinal origin and that it is a fundamental feature of the vertebrate visual system.…”
Section: General Neuronal Processing In the Outer Plexiform Layermentioning
confidence: 50%
“…The second issue concerns the function of spectral coding in HCs, and this has been extensively discussed in Kamermans et al [79] and VanLeeuwen et al [63]. Kraaij et al [66] found that although the spectral sensitivity of HCs is opponent, their combined output to the cones is spectrally very broad and not opponent.…”
Section: (D) Opponent Coding Versus Non-opponent Codingmentioning
confidence: 99%
“…4, no. 2), whose source has not yet been identified (Hardt and Watson, 1999). Presynaptic inhibition has been proposed to enable divisive gain control (Laughlin, 1994;Root et al, 2008;VanLeeuwen et al, 2009). …”
Section: Blocking Of Presynaptic Inhibitionmentioning
confidence: 99%
“…Division, also referred to as gain control, alters the slope of the curve and extends the dynamic output range. These elementary mathematical computations constitute building blocks for both the CNS (Carandini and Heeger, 1994;Peña and Konishi, 2001) and optimal encoding of stimuli in early sensory processing across modalities and species (Barlow andLevick, 1965, Laughlin, 1994;Carandini and Heeger, 1994;Harris et al, 2000;VanLeeuwen et al, 2009;Wen et al, 2009). While the biophysical machinery behind subtractive changes on the level of single cells is well documented (Holt and Koch, 1997;Chance et al, 2002;Gabbiani et al, 2002;Benda and Herz, 2003), most mechanisms proposed to mediate divisive gain control demand a large synaptic background not available in the sensory periphery (Abbott et al, 1997;Chance et al, 2002;Gabbiani et al, 2002;Baca et al, 2008;Rothman et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…1, schematic descriptions). Presynaptic subtraction is supported by measurements of presynaptic calcium currents (VanLeeuwen et al, 2009) and postsynaptic conductance (Laughlin and Osorio, 1989;Weckström et al, 1989;Kamermans et al, 2001). …”
Section: Introductionmentioning
confidence: 99%